2018
DOI: 10.1039/c8cp00416a
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating intra- and intermolecular charge transfer and nonlinear optical response for biphenalenyl biradicaloid dimer under an external electric field

Abstract: An interesting biphenalenyl biradicaloid (IDPL) dimer consisting of both-middle superimposed phenalenyls and both-end nonsuperimposed phenalenyls has been synthesized, and has attracted intensive research interest due to its intra- and intermolecular interactions and semiconductive characteristics. It is significant that under regulation of the external electric field the directional charge transfer (CT) can produce attractive properties. In the present work, the structure and electronic properties of the IDPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…From Table S2, it can be seen that the changes in average amplitudes of the BTCC compound are very small (almost negligible), so the default field amplitude applied by Gaussian is considered reliable here. The FF method has been widely used in recent years for its ability to provide reproducible results of higher-order polarizabilities for several classes of compounds. This method was also found to consist of other NLO calculation methods like TD-SOS, etc …”
Section: Details Of the Applied Computational Methodologymentioning
confidence: 99%
“…From Table S2, it can be seen that the changes in average amplitudes of the BTCC compound are very small (almost negligible), so the default field amplitude applied by Gaussian is considered reliable here. The FF method has been widely used in recent years for its ability to provide reproducible results of higher-order polarizabilities for several classes of compounds. This method was also found to consist of other NLO calculation methods like TD-SOS, etc …”
Section: Details Of the Applied Computational Methodologymentioning
confidence: 99%
“…The first hyperpolarizability density and the natural transition orbital maps were also plotted by the Multiwfn. M06‐2X not only exhibits good performance for calculating electronic structures, but also broadly used to calculate electric properties,,, i.e . dipole moment, polarizability, hyperpolarizabilities.…”
Section: Computational Detailsmentioning
confidence: 99%
“…(2) For substances with clusters or ring structures, such as carbon nanotubes and so on, the molecular structure and electronic structure can be regulated to achieve the researches and developments of new functional materials. [5][6][7][8][9] In 2017, Tian et al 6 found that external electric field can regulate the electronic structure of carbon nanotubes. In 2018, Gao et al 7 found that the external electric field can effectively regulated the first hyperpolarizability of Interesting Biphenalenyl Biradicaloid (IDPL) dimer.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] In 2017, Tian et al 6 found that external electric field can regulate the electronic structure of carbon nanotubes. In 2018, Gao et al 7 found that the external electric field can effectively regulated the first hyperpolarizability of Interesting Biphenalenyl Biradicaloid (IDPL) dimer. This research can be used to further develop nonlinear (NLO) materials, which is of great significance for the application of switching devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation